UV-vis spectroscopic characterization of heterocyclic azines as chemosensors for metal ion detection - Batista, R. M. F. (2015)
The development of colorimetric chemosensors is an area in great expansion due to the simplicity of assay and lower cost compared with others sensing methods. Sensing devices for the analysis of toxic or heavy metal ions play an important role in clinical toxicology, environmental, bioorganic chemistry, bioremediation, and waste management [1]. Until now, most of the chemosensors developed involve laborious and expensive procedures and there is an interest in strategies for single step synthesis, optimizing the efficiency of the chemical reaction and avoiding time-consuming processes of separation and purification. Therefore, the development of a small molecule-based colorimetric chemosensors with simple synthetic and isolation procedures has received much attention in the last decade [2]. The current interest in azine derivatives arises from their wide range of applications in diverse areas such as material and environmental sciences, biomedical, analytical, supramolecular chemistry and catalysis. Additionally, azine ligands bearing N, O and S heteroatoms in their structure should exhibit improved coordination ability [3]. Following our previous work [4], azine ligands functionalized with heterocycles such as thiophene L1, pyrrole L2 and furan L3, were used in a cation chemosensory study in ACN and ACN-water mixtures. L2 exhibited a selective and high sensitive colorimetric response in the presence of Hg(II) and Pd(II) (colourless to yellow or colourless to orange, respectively). [1] (a) Formica, M.; Fusi, V.; Giorgi, L.; Micheloni, M. Coord. Chem. Rev. 2012, 256, 170; (b) Aragay, G.; Pons, J.; Merkoci, A. Chem. Rev. 2011, 111, 3433; (c) Kaur, N.; Kumar, S. Tetrahedron 2011, 67, 9233. [2] (a) Kim, H. N.; Ren, W. X.; Kim, J. S.; Yoon, J. Chem. Soc. Rev. 2012, 41, 3210; (b) Udhayakumari, D.; Suganya, S.; Velmathi, S.; MubarakAli, D. J. Mol. Recognit. 2014, 27, 151. [3] (a) Haldar, R.; Reddy, S. K.; Suresh, V. M.; Mohapatra, S.; Balasubramanian, S.; Maji, T. K. Chem. Eur. J. 2014, 20, 4347; (b) Kennedy, A. R.; Brown, K. G.; Graham, D.; Kirkhouse, J. B.; Kittner, M.; Major, C.; McHugh, C. J.; Murdoch, P.; Smith, W. E. New J. Chem. 2005, 29, 826; (c) Gupta, V. K.; Singh, A. K.; Bhardwaj, S.; Bandi, K. R. Sensors Actuators B: Chem 2014, 197, 264; (d) Huh, H. S.; Kim, S. H.; Yun, S. Y.; Lee, S. W. Polyhedron 2008, 27, 1229. [4] (a) Batista, R. M. F.; Costa, S. P. G.; Raposo, M. M. M. J. Photoch. Photobio. A 2013, 259, 33; (b) Batista, R. M. F.; Oliveira, E.; Costa, S. P. G.; Lodeiro, C.; Raposo, M. M. M. Supramol. Chem. 2013, 26, 71; (c) Batista, R. M. F.; Costa, S. P. G.; Raposo, M. M. M. Sensors and Actuators B: Chem. 2014, 191, 791; (d) Batista, R. M. F.; Costa, S. P. G.; Silva, R. M. P.; Lima, N. E. M.; Raposo, M. M. M. Dyes Pigments 2014, 102, 293.